Communication Apprehension and Eye Contact Anxiety in Video Conferences Involving Teleoperated Robot Avatars: A Subjective Evaluation Study - Mehmood, Faisal; Mahzoon, Hamed; Yoshikawa, Yuichiro; Ishiguro, Hiroshi (Frontiers in Robotics and AI, 2021)
Communication apprehension (CA), defined as anxiety in oral communication, and anxiety in eye contact (AEC), defined as the discomfort felt in communication while being stared at by others, limit communication effectiveness. In this study, we examined whether using a teleoperated robot avatar in a video teleconference provides communication support to people with CA and AEC. We propose a robotic telecommunication system in which a user has two options to produce utterance for own responses in online interaction with interviewer i.e., either by a robot avatar that faces the interviewer, or by self. Two imagination-based experiments were conducted, in which a total of 400 participants were asked to watch videos for interview scenes with or without the proposed system; 200 participants for each experiment. The participants then evaluated their impressions by imagining that they were the interviewee. In the first experiment, a video conference with the proposed system was compared with an ordinary video conference, where the interviewer and interviewee faced each other. In the second experiment, it was compared with an ordinary video conference where the interviewer’s attentional focus was directed away from the interviewee. A significant decrease in the expected CA and AEC of participants with the proposed system was observed in both experiments, whereas a significant increase in the expected sense of being attended (SoBA) was observed in the second experiment. This study contributes to the literature in terms of examining the expected impact of using a teleoperated robot avatar for better video conferences, especially for supporting individuals with CA and AEC.